Understanding Delegated Legislation in The Natural Resources Sector - Fatih, Sholahuddin Al; Safaat, Muchamad Ali; Widiarto, Aan Eko; Al Uyun, Dhia; Nur, Muhammad (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
The formation of statutory regulations is based on the authority to form. The formation of delegated regulations can originate from orders or authority. In the P3 Law, it is stated that delegated regulation is not only limited to (or “there is a space for delegated regulations other than “) Government Regulations, Presidential Regulations, and Regional Regulations, so it becomes hyper-regulation. This happens in laws and regulations in the field of natural resource management. This article aims to explain the condition of existing delegated regulation in the field of natural resources and its impact on the use of natural resources. The results of this research show that the position and types of delegated regulation in the field of natural resources are not only in the form of Presidential Regulations, Government Regulations, Ministerial Regulations, and Regional Regulations but also delegated legislation regulated in Article 8 of the P3 Law, which is not small in number The implications of delegated legislation can provide technically detailed implementing regulations down to the lowest level institutions/institutions. However, delegation not explicitly limited by the delegation criteria causes hyper-regulation by the executive agency through its functional authority. Apart from that, it opens space for unsynchronization between the substance of higher regulations and delegated regulations, thereby causing ineffective use of natural resources. This study recommends that changes be made to the Law on the Establishment of Laws and Regulations, especially concerning its hierarchy.